Can ChatGPT pass the MRCP (UK) written examinations? Analysis of performance and errors using a clinical decision-reasoning framework - Stuart Maitland; Ross Fowkes; Amy Maitland (BMJ Open)
Objective Large language models (LLMs) such as ChatGPT are being developed for use in research, medical education and clinical decision systems. However, as their usage increases, LLMs face ongoing regulatory concerns. This study aims to analyse ChatGPT’s performance on a postgraduate examination to identify areas of strength and weakness, which may provide further insight into their role in healthcare.Design We evaluated the performance of ChatGPT 4 (24 May 2023 version) on official MRCP (Membership of the Royal College of Physicians) parts 1 and 2 written examination practice questions. Statistical analysis was performed using Python. Spearman rank correlation assessed the relationship between the probability of correctly answering a question and two variables: question difficulty and question length. Incorrectly answered questions were analysed further using a clinical reasoning framework to assess the errors made.Setting Online using ChatGPT web interface.Primary and secondary outcome measures Primary outcome was the score (percentage questions correct) in the MRCP postgraduate written examinations. Secondary outcomes were qualitative categorisation of errors using a clinical decision-making framework.Results ChatGPT achieved accuracy rates of 86.3% (part 1) and 70.3% (part 2). Weak but significant correlations were found between ChatGPT’s accuracy and both just-passing rates in part 2 (r=0.34, p=0.0001) and question length in part 1 (r=−0.19, p=0.008). Eight types of error were identified, with the most frequent being factual errors, context errors and omission errors.Conclusion ChatGPT performance greatly exceeded the passing mark for both exams. Multiple choice examinations provide a benchmark for LLM performance which is comparable to human demonstrations of knowledge, while also highlighting the errors LLMs make. Understanding the reasons behind ChatGPT’s errors allows us to develop strategies to prevent them in medical devices that incorporate LLM technology.